Circadian regulation of dengue virus transmission and replication: insights into vector activity and viral dynamics - Zandi, Milad; Mousavi, Fatemeh Sadat (Frontiers in Cellular and Infection Microbiology, 2024)
Dengue fever, caused by dengue virus, poses a significant global health challenge, particularly in tropical regions where Aedes aegypti serves as the primary vector. The circadian clock in Aedes aegypti governs key behavioral and physiological processes, including activity patterns, feeding behaviors, and susceptibility to dengue virus infection. This article explores the influence of circadian rhythms on the mosquito’s ability to transmit dengue virus, emphasizing how the circadian regulation of gene expression, immune responses, and lipid metabolism in the mosquito vector creates temporal windows that affect viral replication efficiency.